The Correlation of Audio-visual Media with Student Learning Outcomes - Zulva Rojauna; Muhammad Arif Setiabudi (Institut Dirosat Islamiyah Al-Amien Prenduan, 2023)
Â The purpose of this research is to define the extent of the relationship between audiovisual means and the results of teaching students to teach Arabic to first-grade students at the Islamic High School